Bacterial populations and volatile organic compounds associated with meat spoilage. (September 2019) - Yushina, Yu K; Bataeva, D S; Zaiko, E V; Machova, A A; Velebit, B
Abstract: The aim of the study was to detect volatile organic compounds acting as markers of spoilage for raw chilled beef stored under vacuum at 4 °C for 15 days. We also determined the relationship of the volatile compounds with microbial and organoleptic properties associated with shelf life. Volatile organic compounds were analysed by multisensory analysis using an electronic nose sensor. Increasing aldehydes, ketones, and alcohols were measured in beef during the storage period. An increase in volatile chemical compounds during storage was correlated with an increased level of Lactobacillus, the predominant group of microorganisms on the beef at the end of the study. Maximum concentrations of volatile chemical compounds were determined at the end of the shelf life of the stored beef. Lactic acid bacteria were the main microorganisms that caused spoilage and are suitable for predicting the shelf life of raw chilled vacuum packaged beef using the electronic nose device at the threshold of 5.0-6.0 log CFU/g.